SATUA BALI SEBAGAI SUMBER BELAJAR BERBASIS KEARIFAN LOKAL DALAM PENGUATAN NILAI-NILAI KARAKTER SISWA - I Wayan Sujana; Komang Ayu Sulistia Wati; Ni Komang Nopiani; Ni Luh Putu Prika Widiani (STKIP Subang, 2026)
This study examines the use of Satua Bali as a local wisdom-based learning resource to strengthen students’ character values. The problem addressed is the limited use of folklore in formal education and the lack of innovative learning media. This study aims to analyze the potential and implementation of Satua Bali in character education. The research uses a literature review method by analyzing relevant sources from 2021–2025. The results show that Satua Bali contains moral values such as honesty, responsibility, cooperation, discipline, and empathy, which can be internalized through contextual learning. The use of storytelling (mesatua), discussion, reflection, and digital media enhances student engagement and supports cognitive, affective, and psychomotor development. Thus, Satua Bali has strong potential as an innovative learning resource for strengthening character and preserving local culture.